Perceived problematic alcohol use in the family and adolescents' stress-related complaints: examining the buffering role of the school's degree of student focus as rated by its teachers - Sara Brolin Låftman; Charlotta Magnusson; Gabriella Olsson; Joakim Wahlström; Bitte Modin (BMC, 2023)
Abstract Background A non-negligible proportion of children grow up with problematic alcohol use in the family. Problematic familial drinking can be regarded as a stressor, and prior studies have consistently reported poorer mental health among adolescents who are exposed. However, it is also of relevance to identify modifiable protective factors which may buffer against stress-related ill-health in this group of adolescents. One context where such factors may be present is the school. The aim of this study is to examine the relationship between perceived problematic familial alcohol use and students' stress-related complaints, and specifically to explore if the school's degree of student focus can buffer against any such negative health consequences of problem drinking at home. Methods Data were drawn from four separate surveys, the Stockholm School Survey (SSS) and the Stockholm Teacher Survey (STS) conducted in 2014 and 2016 among 7,944 students (~ 15-16 years) and 2,024 teachers in 147 Stockholm senior-level school units. Perceived problematic familial alcohol use was measured by one item in the SSS. Stress-related complaints were captured by co-occurring somatic complaints and psychological distress, and reported by students in the SSS. The school's student focus was measured by an index based on teachers' ratings of four items in the STS. A set of covariates at the student and the school level were also included. Two-level binary logistic and linear regression models were performed. Results Perceived problematic familial alcohol use was linked with an increased likelihood of reporting co-occurring somatic complaints as well as psychological distress. Cross-level interactions revealed that the association between perceived problematic familial alcohol use and co-occurring somatic complaints was weaker among students attending schools with stronger teacher-rated student focus. Regarding psychological distress, the association was weaker for students attending schools with intermediate or strong teacher-rated student focus, compared with those attending schools with weaker teacher-rated student focus. Conclusions The findings provide support for the assumption that favourable conditions in schools can buffer against negative health consequences of problematic conditions in the family, thus serving a compensatory role.